Clustering Techniques and Need of Computational Intelligence for Topology Control in Wireless Sensor Networks: an Investigation - M. Kelagadi, Hemantaraj; kumar, Priyatam; Shettar, Rajashekar (International Journal of Engineering and Technology, 2018)
Wireless sensor networks is an accrue of sensing devices usually called nodes that communicate wirelessly. These networks are characterized by limited resources such as power, memory, processing or computation and communicating ability. This gives rise to several challenges in node deployment, scalability and changes in the topological structure. Energy being one of the critical resources in wireless sensor networks, may require the sensor nodes to organise or reorganise which may lead to reduction in the energy consumption of individual and therefore of the entire network as well. A topology control mechanism by means of clustering may help in enhancement of the network performance by being energy efficient and scalable. In this paper a few standard clustering techniques are discussed and possible design objectives are focussed upon. Also a need to employ the techniques to develop â€œadaptiveâ€ capabilities along with clustering techniques are highlighted which may help to improve their functionality and survival aspects along with wise utilization of resources. An inspection of various computationally intelligent models that may be considered for adaptation in topology control is presented in the paper.Â